Midline-1 inhibited high glucose-induced epithelial-mesenchymal transition, fibrosis and inflammation through WNT/β-catenin signaling in benign prostatic hyperplasia - Fu, Xun; Zhang, Hao; Liu, Jiang; Li, Yan; Wang, Zhen; Yang, Shu; Liu, Daoquan; Zhou, Yongying; Chen, Ping; DiSanto, Michael E.; Li, Hongjun; Zhang, Xinhua (Frontiers in Endocrinology, 2025)
Background and objectsBenign prostatic hyperplasia (BPH) is a common disease that impairs the life quality of elderly men. The close relationship of BPH and diabetes has been generally established, however, the exact molecular mechanism remains unclear. Midline-1 (MID1) is an E3 ubiquitin ligase belonging to Tripartite Motif family and its involvement in the initiation and progression of many diseases, such as diabetic kidney disease has been well accepted. This study aims to illuminate the potential impact of high glucose (HG) on prostatic cells and elucidate the molecular role of MID1 in the development of BPH.MethodsIn this work, human prostate specimens and cultured human prostate cell lines (BPH-1 and WPMY-1) were employed. The impact of HG treatment on these two lines was assessed and the expression and localization of MID1, along with its potential downstream target protein phosphatase 2A (PP2A), were determined using multiple experimental methods. MID1-overexpressing cell models were further used to investigate the function of MID1 in regulating inflammation, fibrosis and epithelial-mesenchymal transition (EMT).ResultsHerein we demonstrate diabetic individuals with BPH had lower expression of MID1 and higher expression of the catalytic subunit of PP2A (PP2Ac), larger prostate volume, higher international prostate symptom score (IPSS) and lower Qmax than non-diabetic groups. On a cellular level, HG treatment inhibited the expression of MID1, thus stimulating cellular proliferation and triggering EMT, fibrosis and inflammation of two prostatic cells via enhanced WNT/β-catenin signaling.ConclusionsIn general, our novel data demonstrate targeting MID1 might be a promising area of medical treatment for patients with both BPH and diabetes.